Intercropping - Paparella, Antonio; Petsakos, Athanasios; Davis, Kristin E.; Song, Chun (International Food Policy Research Institute, 2025)
Over the last decades, crop yields in conventional farming and monocropping systems have increased globally, benefiting from advancements in plant breeding and from higher use of inputs, specifically water, fertilizers, and pesticides. However, the environmental, social, and economic sustainability of such high-input/high-output systems is questionable, and this requires revisiting the conventional farming and monocropping systems paradigm. Moreover, conventional agriculture and monocropping significantly impact biodiversity by reducing habitat diversity and increasing environmental degradation. Monocropping promotes genetic uniformity, leading to the decline of traditional crop varieties. Intensive agricultural practices, such as the extensive use of chemical fertilizers and pesticides, result in habitat fragmentation, soil degradation, and loss of soil microbial diversity, which are detrimental to various plants and wild animals.